Influence of Adhesives and Methods of Enamel Pretreatment on the Shear Bond Strength of Orthodontic Brackets - Sanja Jurišić; Gordan Jurišić; Hrvoje Jurić (University of Zagreb. School of Dental Medicine, 2015)
Aim: The objective of present study was to examine influence of adhesives and methods of enamel pretreatment on the shear bond strength (SBS) of orthodontic brackets. The adhesives used were resin-reinforced glass ionomer cements-GIC (Fuji Ortho LC) and composite resin (Transbond XT). Material and Methods: The experimental sample consisted of 80 extracted human first premolars. The sample was divided into four equal groups, and the metal brackets were bonded with different enamel pretreatments by using two adhesives: group A-10% polyacrylic acid; Fuji Ortho LC, group B-37% phosphoric acid; Fuji Ortho LC, group C-self etching primer; Transbond XT, group D-37% phosphoric acid, primer; Transbond XT. SBS of brackets was measured. After debonding of brackets, the adhesive remnant index (ARI) was evaluated. Results: After the statistical analysis of the collected data was performed (ANOVA; Sheffe post-hoc test), the results showed that significantly lower SBS of the group B was found in relation to the groups C (p=0.031) and D (p=0.026). The results of ARI were similar in all testing groups and it was not possible to determine any statistically significant difference of the ARI (Chi- square test) between all four experimental groups. Conclusion: The conclusion is that the use of composite resins material with appropriate enamel pretreatment according to manufacturer's recommendation is the "gold standard" for brackets bonding for fixed orthodontic appliances.